Neutral pathways and heat flux widths in vertical- and horizontal-target EDGE2D-EIRENE simulations of JET. (12th July 2018) - Moulton, D.; Corrigan, G.; Harrison, J.R.; Lipschultz, B.
Abstract: This paper further analyses the EDGE2D-EIRENE simulations presented by Chankin et al (2017 Nucl. Mater. Energy 12 273), of L-mode JET plasmas in vertical–vertical (VV) and Vertical–horizontal (VH) divertor configurations. As expected, the simulated outer divertor ionisation source peaks near the separatrix in VV and radially further out in VH. We identify the reflections of recycled neutrals from lower divertor tiles as the primary mechanism by which ionisation is concentrated on the outer divertor separatrix in the VV configuration. These lower tile reflection pathways (of neutrals from the outer divertor, and to an even greater extent from the inner divertor) dominate the outer divertor separatrix ionisation. In contrast, the lower-tile-reflection pathways are much weaker in the VH simulation and its outer divertor ionisation is dominated by neutrals which do not reflect from any surfaces. Interestingly, these differences in neutral pathways give rise to strong differences in the heat flux density width at the outer divertor entrance: mm in VH compared to mm in VV. In VH, a narrow channel exists in the near scrape-off-layer (SOL) where the convected heat flux, driven by strong flow and thermoelectric current, dominates over the conducted heat flux. The width of this channel sets and is determined by the radial distance between the separatrix and the ionisation peak in the outer divertor.